Charges in Gauge Theories - McMullan, D. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
Recent progress in the construction of both electric, coloured and magnetic charges in gauge theories will be presented. The topological properties of the charged sectors will be highlighted as well as the applications of this work to confinement and infrared dynamics.